Communication—Formation of a Hierarchical Reinforcing Carbon Fiber through Co-Grafting Graphene Oxide and Carbon Nanotube. (21st September 2016) - Zhang, R. L.; Zhang, J.; Wang, C. G.; Li, F. H.; Liu, L.; Cui, H. Z.
Abstract : Model polymer composites containing carbon nanotube (CNTs) and graphene oxide (GO) grafted carbon fiber provides a means to investigate the influence of nanostructures on interfacial properties. The morphology, together with the change of composition was related to the interfacial performance of model composites, which was studied using scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS). In addition, the wetting and surface energy along with contact angles was explored using dynamic contact angle analysis test (DCAT). Furthermore A significant improvement of the interfacial shear strength (IFSS), measured by a micromechanical test derived from the pull-out test, was obtained.